Determination of 44 Organic Pollutants in Groundwater by Gas Chromatography-Triple Quadrupole Mass Spectrometry - YU Lei; ZHANG Xiao-yi (Yankuang ceshi, 2021)
BACKGROUND Organic pollutants such as organochlorine, polycyclic aromatic hydrocarbons and phthalate in groundwater are potential threats to the ecological environment and human health. The development of efficient, accurate and rapid detection methods has practical significance. The organic pollutants in water are extracted by liquid-liquid extraction and solid-phase extraction, for example, and are determined by gas chromatography, gas chromatography-mass spectrometry, and liquid chromatography-mass spectrometry. It is not possible to measure multiple types of organic pollutants with low detection limits. OBJECTIVES To establish a rapid and accurate method for simultaneous determination of multiple semi-volatile organic compounds. METHODS An improved QuECHERS method was proposed to pretreat the sample. The organic phase was taken directly from the water sample after a small amount of organic solvent was added to the water sample without purification. Multi-reaction monitoring mode (MRM) of triple quadrupole mass spectrometer was used for qualitative analysis and internal standard method for quantitative analysis. The improved method achieved the simultaneous determination of 44 organic pollutants. The conditions of mass spectrometry were optimized, the extraction effects of different solvents were compared, and the advantages and disadvantages of traditional methods and QuECHERS were compared. RESULTS The results showed that the linear relationship of 44 organic compounds was good in the concentration range of 1-200μg/L, and the detection limit and recovery of each organic compound met the requirements. CONCLUSIONS The method has the advantages of simple pretreatment, high sensitivity, low background of phthalate and simultaneous determination of multiple types of organics and can be effectively applied to the determination and evaluation of trace organic matter in groundwater.